fyqt.net
当前位置:首页 >> tAn65 +tAn70 >>

tAn65 +tAn70

因为tan 135 = tan(65 + 70) = (tan65 + tan70)/(1- (tan65 * tan70)) 而tan 135 = -1 则-1=(tan65 + tan70)/(1-(tan65 * tan70)) -(1-(tan65 * tan70))=tan65 + tan70 tan65 + tan70 + 1 -(tan65 * tan70)=0 tan65 + tan70 - tan65 * tan70 =-1

tan135=tan(65+70)=(tan65°+tan70°)/1-tan65°tan70°=-1 tan65°+tan70°=-(1-tan65°tan70°) 所以,原式=0

因为 tan 135 = tan(65 + 70) = (tan65 + tan70)/(1- (tan65 * tan70)) 而 tan 135 = -1 则 -1=(tan65 + tan70)/(1-(tan65 * tan70)) -(1-(tan65 * tan70))=tan65 + tan70 tan65 + tan70 + 1 -(tan65 * tan70)=0 tan65 + tan70 - tan65 * tan70...

网站首页 | 网站地图
All rights reserved Powered by www.fyqt.net
copyright ©right 2010-2021。
内容来自网络,如有侵犯请联系客服。zhit325@qq.com